The Adverse Effect of Anxiety on Dynamic Anticipation Performance - Ren, Pengfei; Song, Tingwei; Chi, Lizhong; Wang, Xiaoting; Miao, Xiuying (Frontiers in Psychology, 2022)
Anticipation is a crucial perceptual-cognitive skill in fast-ball sports, and the effect of high anxiety on performance has attracted more attention from sports psychologists. Related studies mainly focus on the effect of anxiety on influencing processing efficiency and attentional control (top-down vs. bottom-up) during information processing in sport. Attentional Control theory (ACT) has been supported by several studies; however, these studies have been criticized by the low ecological validity of task design (such as neglecting the dynamic process of anticipation) and inadequate performance analysis (such as analyzing response accuracy and time separately). Using temporal occlusion paradigm, we tested ACT in a dynamic anticipation process. Eighteen skilled and eighteen less-skilled table tennis players were required to anticipate the serves of opponents under dynamic task constraints (early vs. late occlusion) and anxiety conditions (high vs. low anxiety). High cognitive state anxiety decreased processing efficiency (response time/ response accuracy) for both groups whereas performance effectiveness (response accuracy) did not differ, and negatively affected processing efficiency in early anticipation compared with late anticipation tasks, suggesting that high cognitive state anxiety may have a greater impact on top-down attentional control. Our findings provide support for ACT. Anxiety impairs anticipation efficiency and performance, possibly due to an ineffectively attentional shift from external kinematic cues to internal long-term working memory. Findings have implications for the adaptation of attentional strategies and anxiolytic training.